2021
DOI: 10.1021/acs.jafc.1c05697
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Dietary Intake of Organophosphate Esters via Animal-Origin Food Consumption in China: Results of a Chinese Total Diet Study

Abstract: Although diet is regarded as a major exposure source of organophosphate esters (OPEs), the dietary survey of OPEs in China has been limited. Based on the sixth Chinese Total Diet Study (TDS) conducted during 2016−2019 in 24 of 34 provinces in China, 14 OPEs were detected in 96 food composites from four animal-origin food categories. Twelve OPEs were detected in more than 80% of the samples and 2-ethylhexyl diphenyl phosphate (EHDPP) presented the highest median concentration (1.63 ng/g wet weight (ww)). The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 48 publications
(93 reference statements)
2
15
1
Order By: Relevance
“…This may be due to the lower contents of water (approximately 10% or lower) in the packaged dried fruits analyzed in this study and OPE contamination during industrial processing, which would be discussed in the following section. ΣOPEs in meat in our study exhibited comparable levels with those found for several other studies, in which the median/mean values ranged from 0.410 to 13.6 ng/g ww. , , However, He et al reported much higher levels of ΣOPEs in pork (median: 408 ng/g ww), chicken (272 ng/g ww), and beef (375 ng/g ww) collected from Chongqing, China . They also found elevated ΣOPEs in aquatic products (median: 329 ng/g ww) in comparison with other literature (median/mean: 1.83–11.5 ng/g ww) , , and the present study, which probably resulted from the local pollution of OPEs in their sampling sites.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…This may be due to the lower contents of water (approximately 10% or lower) in the packaged dried fruits analyzed in this study and OPE contamination during industrial processing, which would be discussed in the following section. ΣOPEs in meat in our study exhibited comparable levels with those found for several other studies, in which the median/mean values ranged from 0.410 to 13.6 ng/g ww. , , However, He et al reported much higher levels of ΣOPEs in pork (median: 408 ng/g ww), chicken (272 ng/g ww), and beef (375 ng/g ww) collected from Chongqing, China . They also found elevated ΣOPEs in aquatic products (median: 329 ng/g ww) in comparison with other literature (median/mean: 1.83–11.5 ng/g ww) , , and the present study, which probably resulted from the local pollution of OPEs in their sampling sites.…”
Section: Resultssupporting
confidence: 87%
“…16,[18][19][20][21][22][23]33 However, He et al reported much higher levels of ΣOPEs in pork (median: 408 ng/g ww), chicken (272 ng/g ww), and beef (375 ng/g ww) collected from Chongqing, China. 17 They also found elevated ΣOPEs in aquatic products (median: 329 ng/g ww) 17 in comparison with other literature (median/mean: 1.83−11.5 ng/g ww) 16,[20][21][22][23]33 and the present study, which probably resulted from the local pollution of OPEs in their sampling sites. ΣOPEs in oils in our study were higher than that reported in New York, United States (median: 1.16 ng/g ww), 20 while being 1 order of magnitude lower than that reported in Belgium (mean: 84.4 ng/g ww).…”
Section: Methods Validationmentioning
confidence: 98%
“…Human exposure to OPEs occurs through multiple pathways, and recent studies have shown that the dietary intake of OPEs is an important exposure pathway. There have been increasing reports of OPEs being detected in various categories of food in markets worldwide. He et al calculated the estimated daily intake (EDI) of OPEs via inhalation, dermal contact with dust, and dietary ingestion in an Australian population and found that dietary ingestion contributed the most to the EDI of OPEs . This highlights the need to understand how foods become contaminated by OPEs.…”
Section: Introductionmentioning
confidence: 99%
“…OPFRs can be detected in agricultural products such as grains (rice, corn), vegetables (potatoes, cereals, tomatoes, cabbage, rape, carrots, broccoli, onions, and celery), fruits (apples, bananas, oranges, pears, peaches, citrus, strawberries, and grapes), meat, dairy products, and eggs around the world. , Pregnant women and mothers have a higher daily consumption of OPFRs than other adults, perhaps due to their specialized prenatal and postnatal diets. , Throughout the pregnancy and breastfeeding period, women should have a well-balanced diet and refuel frequently in order to obtain sufficient calories and nutrients. , They may consume more food rich in protein, vitamins, and healthy fats, which maybe contribute to a relative increase in their body burdens of OPFRs . OPFRs can be frequently detected in cereals and meat. For example, China has the highest levels of ∑OPFRs in rice worldwide, as high as 802 ng/g dry weight (dw) . The median concentration of OPFRs in meats and fish collected from a local market in America was higher than those in dairy and cereal products .…”
Section: Resultsmentioning
confidence: 99%